2010
DOI: 10.3168/jds.2010-3281
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and sulfate: Effective alternative hydrogen sinks for mitigation of ruminal methane production in sheep

Abstract: Twenty male crossbred Texel lambs were used in a 2 × 2 factorial design experiment to assess the effect of dietary addition of nitrate (2.6% of dry matter) and sulfate (2.6% of dry matter) on enteric methane emissions, rumen volatile fatty acid concentrations, rumen microbial composition, and the occurrence of methemoglobinemia. Lambs were gradually introduced to nitrate and sulfate in a corn silage-based diet over a period of 4 wk, and methane production was subsequently determined in respiration chambers. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

27
238
4
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 247 publications
(279 citation statements)
references
References 37 publications
(52 reference statements)
27
238
4
10
Order By: Relevance
“…Blood samples were taken when MetHb was expected to be greatest, that is, 3 h after fresh feed was offered (Van Zijderveld et al, 2010), on the day after dietary nitrate was increased (days −27 (25%), −20 (50%), −13 (75%) and −6 (100%)) and then 15 days after maximum nitrate inclusion was achieved (day 8). To assess the long-term effects of feeding nitrate, blood samples were obtained at day 87 and day 101 (128 days after initial inclusion of nitrate).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Blood samples were taken when MetHb was expected to be greatest, that is, 3 h after fresh feed was offered (Van Zijderveld et al, 2010), on the day after dietary nitrate was increased (days −27 (25%), −20 (50%), −13 (75%) and −6 (100%)) and then 15 days after maximum nitrate inclusion was achieved (day 8). To assess the long-term effects of feeding nitrate, blood samples were obtained at day 87 and day 101 (128 days after initial inclusion of nitrate).…”
Section: Methodsmentioning
confidence: 99%
“…Recent interest in the controlled feeding of nitrate has been stimulated because the reduction of nitrate to ammonium in the rumen of adapted animals provides an alternative hydrogen sink to the production of CH 4 (Van Zijderveld et al, 2010). The reduction of nitrate to nitrite and then to ammonium provides an energetically more favourable route for disposal of metabolic hydrogen produced during fermentation of feed carbohydrates in the rumen than the production of CH 4 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research on sheep (Sar et al, 2004;Nolan et al, 2010;van Zijderveld et al, 2010) and cattle (van Zijderveld et al, 2011a and2011b;Hulshof et al, 2012) has shown promising results with nitrates decreasing enteric CH 4 production by up to 50%. Nitrates may be particularly attractive in developing countries where forages contain negligible levels of nitrate and insufficient CP for maintaining animal production.…”
mentioning
confidence: 99%